sj-pdf-1-rci-10.1177_1745499921991958 – Supplemental material for Inclusive education in the diversifying environments of Finland, Iceland and the Netherlands: A multilingual systematic review - Charlotte E. Wolff (10139672); Berglind Rós Magnúsdóttir (10139675); Heidi Huilla (10139678); Sonja Kosunen (10139681); Yannis Tzaninis (10139684); Bowen Paulle (10139687); Sirpa Lappalainen (10139690); Piia Seppänen (10139693) (2021)
Supplemental material, sj-pdf-1-rci-10.1177_1745499921991958 for Inclusive education in the diversifying environments of Finland, Iceland and the Netherlands: A multilingual systematic review by Charlotte E. Wolff, Berglind Rós Magnúsdóttir, Heidi Huilla, Sonja Kosunen, Yannis Tzaninis, Bowen Paulle, Sirpa Lappalainen and Piia Seppänen in Research in Comparative and International Education